SPEAKING ACTIVITES AND GAMES USED IN TEACHING FOREIGN LANGUAGE - Elmuratova, Z.KH. (FAN va JAMIYAT, 2016)
The article is devoted to one of the important language skills in teaching foreign language as speaking. The author of the work deals with the issues of speaking tasks for the learners studying foreign languages. Speaking tasks promote to the better learning of the material in the learning process and let check up students knowledge.